STUDI KOMPARATIF PEMIKIRAN H. HUSIN QADERI DAN H. M. ZURKANI JAHJA TENTANG KONSEP AL ASM AL-HUSN YANG MENUNJUKKAN PERBUATAN ALLAH - M. Zainal Abdin, Norainah Dan (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2014)
This paper compared the tought of al-Asma al-Husna by H. Husin Qader and H.M. Zurkani Jahja. Thereare differences in the tought of the two figures in the delivery of the words of al-Asma al-Husna written in theirwork. H. Husin Qaderi in his book Senjata Mukmin (the Faithfuls weapon) and H.M. Zurkani Jahja inhis book 99 jalan menuju Tuhan (99 ways of finding the God). The findings of this study is H. HusinQaderi thought about al-Asma al-Husna that shows Gods action is the dominant to the practical prayer withzikir, it is appropriate approach to Sufism that he had as well as the community needs are preaching at thattime. H. M. Zurkani Jahja told about al-Asma al-Husna that shows Gods action is the dominant to themoral and spiritual implications, the Sufism approach that he used in accordance with al-Ghazali in his al-Maqsd. Zurkani used simple and easy explanation, it is because he wrote al-Asma al-Husna in a tabloidthen booked, his expectation was the people to behave like the personality of God limited his ability. There aredifferences of tought about al-Asma al-Husna showing the actions of God according to both of them, theirdifference lies in the Gods blessings on His servants. Qaderi more closed, while Zurkani seems more open toGods faithful servant and vice versa to get Gods blessings.